Gastrointestinal disorders among shift workers - Anders Knutsson; Henrik Bøggild (Nordic Association of Occupational Safety and Health (NOROSH), 2010)
OBJECTIVE: Our aim was to review published literature on the association between shift work and gastrointestinal (GI) disorders. METHODS: A systematic review of the literature was conducted of studies that have reported GI symptoms and diseases among shift workers. We used Medline to search for articles from 1966-2009. Next, we manually searched articles in the reference list of each article and previous reviews. RESULTS: Twenty studies met the inclusion criteria. Four of six studies showed a significant association between shift work and GI symptoms, and five of six studies reported an association between shift work and peptic ulcer disease. Two of three studies showed an association between shift work and functional GI disease. Only a few studies have examined gastroesophageal reflux disease, chronic inflammatory bowel diseases, or GI cancers in relation to shift work. CONCLUSIONS: Our general judgment is that shift workers appear to have increased risk of GI symptoms and peptic ulcer disease. However, control for potential confounders (eg, smoking, age, socioeconomic status, and other risk factors) was often lacking or insufficient in many of the studies we examined.